Potential Thematic Campaign for Lampung Tourism - Hasan Basri (UBL, 2013)
Campaign program for the development of the tourism industry has been commonly used. It is still necessary to design campaign programs with different specifications which are based on the uniqueness of a tourist attraction. There is a trend about tourist attraction visited mostly by foreign tourists, but actually rarely visited by the public in general. The indication is people are no longer just travel for a vacation, but there is a new reason to get there as the distribution and development of a hobby.Attractions that have such privilege seemas if to get the grace, there is no need to build from the starting point, just need to maximize their potential. Such conditions in Lampung Province are found in several places such as Tanjung Setia Krui beach, in west Lampung with waves that are rarely found by surfing enthusiasts from around the world. There is also Teluk Kiluan serving familiarity of dolphin life. In the context of natural grace, that privilege needs an extra support campaign program that concentrates on a specific theme as well, which is not randomly widespread but effective.Thematic campaign program can optimize a potential unique tourist attraction that has already existed. In theprogram, the campaignis designed with a central theme that is set from the privilege sights, then the message is designed in such a way, so that the public affection is more striking in the component of behavior. What is important in the campaign strategy is to note the specification of targeted audience. In addition, the thematic campaign will bear programs that are not randomly widespread but more scalable premises that must carry out monitoring and evaluation as good as possible. It is because there is a possibility to modify the executed strategy in the course of the campaign program.